TWO DIMENSIONAL NULL SCROLLS IN R1n AND MASSEY'S THEOREM - Oztekin, Handan B.; Ergut, Mahmut (Int Electronic Journal Geometry, 2009)
In this study, we investigated new characteristic properties for two dimensional null scroll in the n-dimensional Lorentzian space R-1(n) and we examined the sufficient and necessary conditions for the null scroll M is to be totally geodesic. We also gave the Massey's Theorem for the two dimensional null scroll in R-1(n) which is well known for the ruled surfaces in the Euclidean 3-space [4, 5].
Keywords: Null scroll; Massey's Theorem